Alan Duff's Once were warriors - A. Holm (Law Text Culture, 1995)
Duff, Alan 1994 Once Were Warriors University of Queensland Press St Lucia (first published 1990) For many years New Zealand has had an international image as a nation whole and harmonious, with an enviable record of race relations. Maori activism centred on contestation of land ownership through the 'Treaty of Waitangi' has been recast to celebrate New Zealand race relations (thus maintaining 'national' mythologies) or as the irrational actions of radicals, rather than revealing a history of violence, oppression and dispossession. Conversely, when conflict has become visible it has been treated as a moment separated from what Ranginui Walker calls 'the endless struggle of the Maori for social justice, equality and self-determination' (Walker 1990: 10).